A Comparison of Modality Tests Based on Real Life Data Applications: A Comparison of Modality Tests Based on Real Life Data Applications - Arshad, Rana Muhammad Imran; Imran, Shahina; Jamal, Farrukh; Ozel, Gamze (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Nonparametric tests for the modality are known as distribution-free tests to evaluate the evidence about homogeneity in a population. Silverman’s bandwidth test by Silverman [1], the Hartigan’s dip test by Hartigan [6],Hartigan and Hartigan [7], Proportional Mass (PM) test by Cavallo and Ringobon [4] and Excess Mass (EM) test by Muller and Sawitzki [9] are very popular modality tests in literature. The researchers of these tests claimed that their tests perform well to detection of unimodality, bimodality and multimodality. This study focusses on the comparison of these tests based on real data applications. The results show that Silverman’s bandwidth test is the best test for detecting modality whether it is unimodality, bimodality or multimodality.